In the shadow of the Mexican revolution : contemporary Mexican history, 1910-1989 - Aguilar Camín, Héctor, 1946- (Translations from Latin America series., 1993)
Hector Aguilar Camin and Lorenzo Meyer, two of Mexico's leading intellectuals, set out to fill a void in the literature on Mexican history: the lack of a single text to cover the history of contemporary Mexico during the twentieth century, from the conditions that set in motion the Mexican Revolution of 1910 to the most recent presidential elections in 1988. A la sombra de la Revolucion Mexicana, now available in English as In the Shadow of the Mexican Revolution, offers a sweeping account of Mexico's history since 1910: seventy-nine years of change and continuity, innovation and reiteration. It covers the Mexican Revolution itself, the gradual consolidation of institutions, the Cardenas regime, the "Mexican economic miracle" and its subsequent collapse, and the recent transition toward a new historical period. Both authors are vigorous and influential commentators on contemporary events in Mexico, and both have political influence (although they deliver it in different ways: Aguilar Camin defends the current regime, while Meyer critiques it). Presenting contemporary Mexican history from a Mexican point of view, they offer a comprehensive and authoritative study of Mexico's turbulent recent history, a history that increasingly intertwines with that of the United States. Given the level of interest in Mexico - likely to increase still more as a result of the recent liberalization of trade policies - this volume will be useful in affording U.S. readers an intelligent, comprehensive, and accessible study of their neighbor to the south. With prose that is appealing for both its humor and sharpness, the book should interest an informed general readership, as well as being attractive for classroom adoption